Self-Adaptive Security for SLA Based Smart Contract - Singh, Irish; Lee, Seok Won (Proceedings of the IEEE International Conference on Requirements Engineering, 2021)
The current smart contracts development practices do not follow a standard security development process to understand and explore the security vulnerabilities and attacks in smart contracts. We propose a self-adaptive security modeling approach for modeling and analyzing Service Level Agreement (SLA) based smart contracts using attack scenarios and goal models. There are many security vulnerabilities and bugs in the smart contract due to inconsistencies in the design of smart contracts. The objective of the proposed research is to help the smart contract security requirements designers and developers to understand the security vulnerabilities, concerns, and to propose a self-adaptive security approach to provide countermeasures to detect and mitigate these attacks in the SLA smart contract in the domain of Blockchain-Based Cloud (BBC).
Keywords: current; Block-chain; Development practices; Development process; Modeling approach; Security attacks; Security modeling; Security vulnerabilities; Self adaptive securities; Servicelevel agreement (SLA); Blockchain; Cloud; Self-Adaptive Security; Service Level Agreement; Smart Contract